2021
DOI: 10.1152/ajpgi.00058.2021
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate scores of advanced fibrosis in NAFLD/NASH do not predict mortality in patients with medium-to-high cardiovascular risk

Abstract: Background: Untreated NAFLD may have significant consequences including an increase in mortality and cardiovascular injury. Thus, early detection of NAFLD is currently believed not only to prevent liver related but also cardiovascular mortality. However, almost nothing is known about co-existing NAFLD in patients with coronary artery disease (CAD). Aims: We investigated the impact of surrogates scores of fibrosis in NAFLD in a large cohort of patients referred to coronary angiography. Results: Modelling the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Other study also reported that surrogate risk scores for NAFLD-related fibrosis, such as FIB-4 do not add information in assessing the CVD events in patients with CAD proven by angiography. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Other study also reported that surrogate risk scores for NAFLD-related fibrosis, such as FIB-4 do not add information in assessing the CVD events in patients with CAD proven by angiography. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Advanced liver fibrosis is the major and most common pathophysiology of many chronic liver diseases, which frequently coexist and contribute independently to each condition. Previous studies found that NAFLD increased the risk of CAD, HF and AF independently of shared metabolic risk factors 22,23,24,25,32,34 . Furthermore, the risk of incident cardiovascular events correlates with the severity of NAFLD histology, suggesting a possible dose–response relationship 35 .…”
Section: Discussionmentioning
confidence: 94%
“…This meta-analysis included twelve cohort studies (eleven perspectives and one retrospective) involving 25,252 patients with established cardiovascular disease (nonvalvular atrial fibrillation (AF), 20 myocardial infarction (MI), 21 coronary artery disease (CAD) [22][23][24][25] and heart failure (HF) [26][27][28][29][30][31] ). Six investigations were carried out in Japan, 20,26,27,28,29,30 four in China [21][22][23][24] and one each in Germany 25 and the United States. 31 The sample sizes in these studies ranged from 116 to 5143.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations